Counting the cost of an outbreak of carbapenemase-producing Enterobacteriaceae: an economic evaluation from a hospital perspective. (March 2017) - Otter, J.A.; Burgess, P.; Davies, F.; Mookerjee, S.; Singleton, J.; Gilchrist, M.; Parsons, D.; Brannigan, E.T.; Robotham, J.; Holmes, A.H.
Abstract: Objective: To perform an economic evaluation on the cost associated with an outbreak of carbapenemase-producing Enterobacteriaceae (CPE). Methods: We performed an observational economic evaluation of an outbreak of CPE (NDM-producing Klebsiella pneumoniae ) affecting 40 patients in a group of five hospitals across three sites in West London. Costs were split into actual expenditure (including anti-infective costs, enhanced CPE screening, contact precautions, temporary ward-based monitors of hand and environmental practice, and environmental decontamination), and 'opportunity cost' (staff time, bed closures and elective surgical missed revenue). Costs are estimated from the hospital perspective over the 10-month duration of the outbreak. Results: The outbreak cost €1.1m over 10 months (range €0.9–1.4m), comprising €312 000 actual expenditure, and €822 000 (range €631 000–€1.1m) in opportunity cost. An additional €153 000 was spent on Estates renovations prompted by the outbreak. Actual expenditure comprised: €54 000 on anti-infectives for 18 patients treated, €94 000 on laboratory costs for screening, €73 000 on contact precautions for 1831 contact precautions patient-days, €42 000 for hydrogen peroxide vapour decontamination of 24 single rooms, €43 000 on 2592 hours of ward-based monitors, and €6000 of expenditure related to ward and bay closures. Opportunity costs comprised: €244 000 related to 1206 lost bed-days (range 366–2562 bed-days, €77 000–€512 000), €349 000 in missed revenue from 72 elective surgical procedures, and €228 000 in staff time (range €205 000–€251 000). Reduced capacity to perform elective surgical procedures related to bed closures (€349 000) represented the greatest cost. Conclusions: The cost estimates that we present suggest that CPE outbreaks are highly costly.